2016
DOI: 10.1016/j.euroneuro.2015.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intranasal oxytocin on neural processing within a socially relevant neural circuit

Abstract: Dysregulation of the Mirror Neuron System (MNS) in schizophrenia (SCZ) may underlie the cognitive and behavioral manifestations of social dysfunction associated with that disorder. In healthy subjects intranasal (IN) oxytocin (OT) improves neural processing in the MNS and is associated with improved social cognition. OT's brain effects can be measured through its modulation of the MNS by suppressing EEG mu-band electrical activity (8-13 Hz) in response to motion perception. Although IN OT's effects on social c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Importantly, after OXT administration, alpha/mu and beta rhythms had a general suppressive effect that was widespread across the scalp (viz not only on brain areas of the somato-motor cortex), something that was interpreted as an effect on a broader network, in which mirror/motor and attentional mechanisms can be with difficultly disentangled (Perry et al, 2010 ). A similar experiment was conducted by Singh et al ( 2015 ), also in Schizophrenia patients, and replicated the diffused effect of OXT in the brain. Lastly, Hepker ( 2016 ) tested how OXT affects mirror neuron activity in a hand-gesture experiment and encountered greater mu rhythm suppression, in accordance with other experiments, but this time for a biological movement directly involved in language processing.…”
Section: Dynome—cognomesupporting
confidence: 71%
“…Importantly, after OXT administration, alpha/mu and beta rhythms had a general suppressive effect that was widespread across the scalp (viz not only on brain areas of the somato-motor cortex), something that was interpreted as an effect on a broader network, in which mirror/motor and attentional mechanisms can be with difficultly disentangled (Perry et al, 2010 ). A similar experiment was conducted by Singh et al ( 2015 ), also in Schizophrenia patients, and replicated the diffused effect of OXT in the brain. Lastly, Hepker ( 2016 ) tested how OXT affects mirror neuron activity in a hand-gesture experiment and encountered greater mu rhythm suppression, in accordance with other experiments, but this time for a biological movement directly involved in language processing.…”
Section: Dynome—cognomesupporting
confidence: 71%
“…We speculate that it could reflect the oxytocinenhancing effect of antipsychotics. 64,65 Indeed, oxytocin has been shown to enhance MNS activity in healthy individuals 66,67 and in patients with schizophrenia, 68 and to increase imitation. 69,70 Future studies could explore this relationship further.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms through which oxytocin exerts its effects have yet to be fully understood, studies have shown that it could be related to anxiety reduction, affiliative motivation, and perceptual selectivity [16]. However, only a few studies in normal volunteers [17,18], combat veterans under threat [19], and schizophrenia [20] have used mu suppression to evaluate the effects of oxytocin on the mirror neuron system.…”
Section: Introductionmentioning
confidence: 99%